Variation in land use/land cover and aircraft sound levels around Abu Dhabi International Airport - Khaula A.S. ALKAABI; M. M. YAGOUB (European Journal of Geography)
More than 23 million passengers passed through the terminals of Abu Dhabi International Airport (AUH) during 2017, with an average of over 14,000 flights each month that increase levels of aircraft sounds and vibrations associated with airliners. This paper focuses on analyzing the variation in land use and aircraft sound levels around AUH in order to understand how the local community has been affected and provide policy recommendations. The land-use change data around the AUH, extracted from secondary data sources using remote sensing and geographic information systems, show a major increase in urban areas during the twenty-year period considered (1993–2013), which is mainly due to the increase in population and growth of the tourism industry. While the current noise levels around AUH are found to comply with the standards of the Federal Aviation Administration, we recommend that authorities avoid allowing public institutions to be built near aircraft flight paths.